Masyarakat Rasional dan Tantangan dalam Menghadapi Artificial Intelligence: Analisis Kritis Platform Search Engine - Noorzeha, Fuad; Supartiningsih, Supartiningsih; Sutono, Agus (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2024)
AI has benefits for the development of human life. However, artificial intelligence is also threatening and risky for the future of humanity. This AI can be seen in the influence and impact that occurs in all human activities. AI is human work that is indirectly taken over by an algorithm structure called artificial intelligence. The rational manipulation produced by AI forces humans to try to find their identity. The challenge of AI seems to be the freedom of humans as rational humans. This qualitative research uses Max Horkheimer as a formal object and artificial intelligence as a material object. This research was conducted using two methodical elements; phenomenology as the author’s attempt to uncover social challenges in the face of AI. Induction is used as a conclusion drawing from some data, researchers found the results of research, namely society in this modern era how to determine the function of AI as its identity as a rational society.